"The Unsung Heroes of Ireland": Masculinity, Gender, and Breadwinning among Ireland's "Euro-Commuters". (August 2020) - Ralph, David
Here I examine the masculinity/breadwinning nexus among a group of intra-European migrants, namely, those who commute for work between European states—or Euro-commuters. I focus specifically on professional male Euro-commuters, who live in the Republic of Ireland but work in another European Union (EU)-28 country. Examining their mobility decision-making process, I argue that the impetus behind Euro-commuting is strongly influenced by normative gender-based expectations around masculinity and breadwinning. Threatened with socioeconomic insecurity in austerity-hit Ireland, respondents struggled to sustain strongly gendered identities as their families' primary breadwinners. Consequently, by securing professional white-collar work in another EU-28 country, not only is downward social mobility from the Irish middle-class offset but also equally so is the threat to their firmly held masculine breadwinner identities. In securing this employment, then, my respondents were compensating for what they felt to be their "failed" masculinity during bouts of underemployment or unemployment; they were now performing masculinity "successfully" by working overseas. Effectively, Euro-commuting is a further means of reasserting hegemonic gender-based identities as middle-class male breadwinners. This mobility thereby contributes to novel patterns of reproducing privileged gender subjectivities.